توظيف الأساليب الحديثة في مجال تكنولوجيا التعليم بكلية العلوم والتكنولوجيا في جامعة محمد بوضياف ـ المسيلةـ - بلعباس, عبد الحميد (جامعة الوادي - University of Eloued, 2017)
واجهت العملية التربوية في النصف الثاني من القرن العشرين عدة ضغوطات وتحديات. فالانفجار المعرفي والانفجار السكاني وثورة المواصلات والاتصالات والثورة التكنولوجية وما يترتب عليها من سرعة انتقال المعرفة، كلها عوامل تضغط على المؤسسة التعليمية من اجل مزيد من الفعالية والاستحداث والتجديد لمجاراة هذه التغيرات. ولقد لجأت دول العالم إلى استخدام التقنيات بدرجات متفاوتة لمواجهة هذه الضغوط والتحديات ومحاولة تطبيقها في مختلف المراحل التعليمية بما في ذلك الجامعية منها، و جامعة المسيلة بمختلف كلياتها تسعى للحصول على هذه التقنية وتوظيفها في العملية التعليمية وكنموذج لذلك قمنا بدراسة على كلية العلوم و التكنولوجيا.The educational process in the second half of the twentieth century faced several pressures and challenges. The explosion of knowledge, the explosion of population, the revolution of communication, the technological revolution and the consequent speed of knowledge transfer all exert pressure on the educational institution for more efficiency, innovation and innovation to cope with these changes. The countries of the world resorted to the use of technologies to varying degrees to meet these pressures and challenges and try to apply them in different stages of education, including university And the University of M’sila in various faculties seek to acquire this technology and employment in the educational process and as a model, we have studied the Faculty of Science and Technology
مقال
Keywords: التكنولوجيا ، التعليم .، التقنية ، التربية ، الطلبة; Technology, Education, Education, Students